Blood pressure and cardiac autonomic adaptations to isometric exercise training: A randomized sham‐controlled study. Issue 2 (27th January 2022) - Decaux, Anthony; Edwards, Jamie J.; Swift, Harry T.; Hurst, Philip; Hopkins, Jordan; Wiles, Jonathan D.; O'Driscoll, Jamie M.
Abstract: Isometric exercise training (IET) is increasingly cited for its role in reducing resting blood pressure (BP). Despite this, few studies have investigated a potential sham effect attributing to the success of IET, thus dictating the aim of the present study. Thirty physically inactive males ( n  = 15) and females ( n  = 15) were randomly assigned into three groups. The IET group completed a wall squat intervention at 95% peak heart rate (HR) using a prescribed knee joint angle. The sham group performed a parallel intervention, but at an intensity (<75% peak HR) previously identified to be inefficacious over a 4‐week training period. No‐intervention controls maintained their normal daily activities. Pre‐ and post‐measures were taken for resting and continuous blood pressure and cardiac autonomic modulation. Resting clinic and continuous beat‐to‐beat systolic (−15.2 ± 9.2 and −7.3 ± 5.6 mmHg), diastolic (−4.6 ± 5 and −4.5 ± 5.1), and mean (−7 ± 4.2 and −7.5 ± 5.3) BP, respectively, all significantly decreased in the IET group compared to sham and no‐intervention control. The IET group observed a significant decrease in low‐frequency normalized units of heart rate variability concurrent with a significant increase in high‐frequency normalized units of heart rate variability compared to both the sham and no‐intervention control groups. The findings of the present study reject a nonspecific effect and further support the role of IET as an effective antihypertensive intervention. Clinical Trials ID: NCT05025202. Abstract : Isometric exercise training is increasingly recognized as a powerful alternative exercise intervention for the management of hypertension. Our findings suggest that the clinically significant reductions in blood pressure following isometric exercise training are the result of the intervention and not due to other nonspecific factors, such as the placebo effect.